Potential psychological implications of road accidents during festive and peak travel periods in South Africa - Miyambu, Gezani Richman; Nkoane, Simon Setsweke; Seeletse, Solly Matshonisa (Edelweiss Applied Science and Technology, 2025)
This study explores the psychological implications of road accidents during South Africa’s festive and Easter periods, focusing on how psychological factors contribute to accidents and affect victims, families, and emergency responders. A literature-based research approach was used, guided by Systems Theory, Risk Management Theory, and Resource-Based Theory. Peer-reviewed studies and reports from 2019–2025 were synthesized to examine the intersection of psychological, environmental, and systemic factors influencing road safety. The study found that stress, fatigue, aggression, distraction, and mental illness are key psychological contributors to road accidents. The psychological consequences include post-traumatic stress disorder, depression, anxiety, and burnout among emergency responders. Evidence supports the need for early intervention, public awareness, and improved mental health support during high-risk travel periods. Integrating mental health care into road safety strategies, applying predictive analytics for resource allocation, and implementing targeted public education can mitigate psychological harm and enhance resilience among road users and responders during peak travel seasons.